Infamous eaudiobook Medieval dewarenne series, book 2. - Henley, Virginia (Medieval DeWarenn, 2007)
A Romantic Times Lifetime Achievement Award winner, Virginia Henley crafts sultry tales of seduction set during the High Middle Ages. Strong-willed and free spirited, Marjory de Warenne long ago gave her body and soul to the charming and beguiling Guy de Beauchamp. But her family never approved of the pairing. Now on the eve of war-and an arranged marriage to another suitor-Jory yearns for the man who could make all of her dreams come true.